Efficacy of Hypertonic Saline Solution to Achieve Persistent Intraoperative Intracranial Hypotension in Endoscopic Endonasal Transsphenoidal Surgery - A. B. Kurnosov; M. A. Kutin; O. I. Sharipov; P. L. Kalinin; D. V. Fomichev; N. V. Malevanaya (Неотложная медицинская помощь, 2020)
Abstract. The use of endoscopic transsphenoidal access is an effective and safe method for the surgical treatment of pituitary adenomas (PA). In endoscopic transsphenoidal surgeries, there is a need to control intracranial pressure (ICP) for reposition and expansion of the tumor capsule. Currently, the main method for reducing ICP in transsphenoidal surgery is installation of an external lumbar drainage, which is associated with a number of complications.Aim of study. To improve the results of surgical treatment of patients with hypertension using hypertonic saline solution (HSS).Material and methods. The study included 89 patients, who were devided into two groups: Group A — control group (n=25), where the lumbar drainage was installed for invasive intraoperative measurement of the dynamics of ICP parameters at the main stages of the operation (HSS was not administered in these patients); Group B — study group (n=64), where the efficacy of noninvasive regulation of the tumor capsule position using intravenous HSS was assessed, in addition, lumbar drainage was installed in 25 patients of group B, as well as in group A, for invasive measurement of ICP (the dynamics of ICP changes at the main stages of the operation was measured), and the dynamics of changes in the electrolyte composition of the plasma during the first days after the administration of the HSS was monitored as well.Results. In Group B, there was a more significant decrease in ICP in the course of HSS (on average by 22.49 mm Hg) compared to Group A, where the decrease in ICP was 14.23–8,46 mm Hg (from 13.62±1.36 mm Hg, p<0.05). After intravenous administration of HSS, the plasma composition changed as expected (the concentrations of Na+ and Cl increased on average to 150±0.71 mmol/L and 118.3±1.06 mmol/L, respectively, which slightly exceeded the average statistical norm, K + slightly decreased within the average statistical norm), during the first day there was a normalization of the above laboratory parameters .This technique was used to obtain patent No. 2669924 “A method for regulating the position of a tumor capsule in endoscopic transsphenoidal surgery of pituitary adenoma”.Conclusion. The use of HSS is a safe noninvasive technique for expansion of the tumor capsule during operations to remove pituitary adenomas using transsphenoidal endoscopic access. It should be noted that this method is most appropriate in situations not associated with the risk of developing intraoperative liquorrhea.